2021
DOI: 10.1177/21582440211018683
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Affective Components of Verbal Self-Concepts and Internal/External Frame of Reference Within the Multidimensional Verbal Domain

Abstract: Most researchers have studied students’ academic self-concept within native language and mathematics, indicating the multidimensional nature of academic self-concept. However, there is a shortage of studies that examined the twofold multidimensional structure of verbal self-concept within the internal/external frame of reference (I/E) model of two foreign languages. This study aims to examine affective and cognitive components of English and Russian self-concepts for defining the separation or conflation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Of the different types of the external criteria, the short-term educational outcome-academic achievement-has been the one most frequently used. Studies have reported that consistently in various academic domains, the competence and affect components of ASC have different relations with academic achievement among students at different stages of schooling and in various school domains, including students in primary schools (Arens et al, 2011: general school, verbal, and math;Arens and Preckel, 2018: verbal, math, and physical education;Lohbeck, 2019: verbal and math;Schneider and Sparfeldt, 2020: verbal and math) and in secondary schools (Abu-Hilal et al, 2013: math and science;Arens et al, 2014b: verbal and math;10.3389/fpsyg.2022.1001187 Frontiers in Psychology 04 frontiersin.org Kadir et al, 2017: verbal, math, and physics;Marsh et al, 2013: math and science;Karimova and Csapó, 2021: verbal and foreign language). For instance, with German primary school students, Arens et al (2011) found that consistently across three domains, namely general school, German, and math, the correlations between competence and achievement were doubled those between affect and achievement in the matching domains.…”
Section: The Between-network Approach To Testing the Twofold Multidim...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the different types of the external criteria, the short-term educational outcome-academic achievement-has been the one most frequently used. Studies have reported that consistently in various academic domains, the competence and affect components of ASC have different relations with academic achievement among students at different stages of schooling and in various school domains, including students in primary schools (Arens et al, 2011: general school, verbal, and math;Arens and Preckel, 2018: verbal, math, and physical education;Lohbeck, 2019: verbal and math;Schneider and Sparfeldt, 2020: verbal and math) and in secondary schools (Abu-Hilal et al, 2013: math and science;Arens et al, 2014b: verbal and math;10.3389/fpsyg.2022.1001187 Frontiers in Psychology 04 frontiersin.org Kadir et al, 2017: verbal, math, and physics;Marsh et al, 2013: math and science;Karimova and Csapó, 2021: verbal and foreign language). For instance, with German primary school students, Arens et al (2011) found that consistently across three domains, namely general school, German, and math, the correlations between competence and achievement were doubled those between affect and achievement in the matching domains.…”
Section: The Between-network Approach To Testing the Twofold Multidim...mentioning
confidence: 99%
“…Defined as "a person's perception of himself formed through his experience with his environment and influenced especially by environmental reinforcements and significant others" (Shavelson et al, 1976, 411), self-concept (SC) is widely acknowledged as an important psychological construct, vital in all parts of human life, and it has been researched in a variety of fields, including education, psychology, sport sciences, mental health, and many more (Marsh and Craven, 2006;Onetti-Onetti et al, 2019;Karimova and Csapó, 2021;Henning et al, 2022;Melguizo-Ibáñez et al, 2022). For decades, empirical research has shown that having positive SC is beneficial for many areas of human functioning (Marsh et al, 2017): fighting against anxiety and distress, for strengthening confidence and resilience, and for being adaptive to handle complex problems and situations (Coopersmith, 1960;Harter, 1990;Dodgson and Wood, 1998;Sommer and Baumeister, 2002), and thus enables many human potentials (Marsh and Craven, 2006;Marsh and O'Mara, 2008).…”
Section: Introductionmentioning
confidence: 99%